Concentration-dependent aggregation behavior of asymmetric cationic surfactant hexyldimethyloctylammonium bromide - Hyde, A.; Fujii, S.; Sakurai, K.; Phan, Chi; Yusa, S. (2017)
© 2017 The Chemical Society of Japan. The aggregation behavior of the asymmetric cationic surfactant, hexyldimethyloctylammonium bromide (C 6 C 8 DAB), was analyzed by dynamic light scattering (DLS) and transmittance measurements at various surfactant concentrations. DLS measurements showed that large aggregates appeared spontaneously as the solution was diluted toward the critical micelle concentration (CMC), accompanied by the solution turning turbid.